Evaluasi Kualitas Usability Sistem Informasi Manajemen Rumah Sakit dengan Metode Heuristic Evaluation dan End User Computing Satisfaction - Fadhil, Muhammad; Irman Effendy (JSAI (Journal Scientific and Applied Informatics), 2024)
This study seeks to assess the usability of the Hospital Management Information System (SIMRS) in OKU RSUD Timur through the application of Heuristic Evaluation and End-User Computing Satisfaction (EUCS) methodologies. The implementation of SIMRS began in 2018 with the aim of improving the operational efficacy of the healthcare facility. However, various technical challenges, including system malfunctions and inaccuracies in data entry, continue to hinder the effectiveness of its utilization. The research methodology used is quantitative descriptive, utilizing data collected through a questionnaire distributed to 78 personnel in OKU RSUD Timur. Data analysis revealed that the average user satisfaction score on EUCS was 81.74%, while the Heuristic Evaluation produced an average score of 82.58%. Both evaluative methodologies indicate that the usability of SIMRS can be categorized as commendable, although the Heuristic Evaluation showed slightly superior results. Given these findings, usability improvements can be directed at refining aesthetic and minimalist features, as well as strengthening system controls and security measures. This investigation contributes to the body of empirical evaluations related to the usability of MIS in health care institutions, thereby encouraging improvements in the quality of health information systems.